Elémire Zolla e “Nuovi Argomenti”: il laboratorio di Eclissi dell’intellettuale - Elena Grazioli (Fabrica Litterarum Polono-Italica)
The essay examines Elémire Zolla’s contributions to “Nuovi Argomenti”. It highlights how the journal was considered a ‘privileged venue’ for the publication of his works by publishing the core content of Eclissi dell’intellettuale, despite Zolla’s intense work during the same period at “Tempo Presente”. More broadly, it analyzes Zolla’s different contributions to Carocci’s and Moravia’s periodical, ranging from responses to surveys to the more literary essay Proust e la politica di potenza. It aims to contextualize his early work in Rome within the general trajectory of his research and scholarly interests, particularly focusing on critical theory concerning his contemporary society.